USE OF FLIPPED CLASSROOM INSTRUCTIONAL STRATEGY FOR IMPROVING STUDENTS’ ACADEMIC ACHIEVEMENT IN COLLEGES OF EDUCATION - Kadiri, Hassan (IJIET (International Journal of Indonesian Education and Teaching), 2024)
The increasing use of social media by students in tertiary institutions is posing challenges to the effectiveness of traditional lecture methods and students’ learning outcomes. Students nowadays have become socially diversified and spend more time on social media at the expense of individual learning. Hence, there is a need for the incorporation of the internet-based means of communication into the teaching-learning process. Therefore, this study integrated social-media platforms into teaching-learning activities in the college of education through the use of flipped classrooms with the specific aim of determining its effect on students’ academic achievement. The study adopted a quasi–experimental research design and a sample of 262 Economics students from two Colleges of Education was used. The experimental group was exposed to flipped classroom instruction while the control group was taught using the conventional lecture method. Data were collected with the use of an achievement test while descriptive statistics, t-test, and ANCOVA were used to analyze data. Findings from the study revealed a significant difference between the mean achievement scores of students taught Economics using flipped classroom instruction and those taught using conventional lecture methods (p = 0.00 0.05). Also, the ability was found to have a significant effect on the academic achievement (p = 0.00 0.05) of students in the flipped class. However, the study revealed that the effect of gender on the academic achievement of students taught with a flipped classroom instructional strategy was not significant (p = 0.765 0.05). Thus, it was concluded that flipped classroom instruction enhanced students’ academic achievement more than the conventional lecture method based on these findings. Therefore, the study recommended the use of flipped classrooms in colleges of education for the improvement of students’ academic achievement.